E-LEARNING DENGAN PENDEKATAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA - Thomas, Partono; Setiaji, Khasan (Fakultas Ekonomi, Universitas Negeri Semarang, 2014)
Students in the first semester got difficulty to adapt the learning process in the university (student-oriented) which are different with the senior high school (teacher-oriented). Thus, the lecturer needed to solve the problem to sharpen studentsâ independence by using Jigsaw, a cooperative learning. Then, e-learning was also an important factor to spread the knowledge widely to students. Thus; the combination of Jigsaw and e-learning was expected to improve studentsâ achievement. The subjects of the study were 40 Economics education students in bachelor degree (S1), Unnes in Curriculum Review class. The objective of the study was to minimize the mistake, improve the studentsâ interest and study result in understanding the concept of the Standard of National Education through independent learning strategy based on e-learning and cooperative learning of Jigsaw. The result of study showed that studentsâ activities, interest, attention, participation in discussion and presentation in the classroom increased significantly with the mean 4.14. Then, studentsâ test results increased from pre-test which was only 74 then rose to 79 in the 1st cycle and 81 in the 2nd cycle with the level of completeness was 87.5%. Furthermore, students thought that the strategy was very good with the score 4.12